Economic Diplomacy Activities in The Association of Indonesian Export Entrepreneurs (GPEI) West Java - Elsa Fitriani Ahmad; Neng Lina Rachmawati; Yani Suryantini; Muhammad Danuri (Trasearch (Training, Research and Academy Society, 2025)
Economic diplomacy is a crucial element in strengthening exports and investments in Indonesia, especially amid globalization challenges and international competition. The Indonesian Exporters Association (GPEI) of West Java plays a strategic role as a facilitator between the government, business actors, and international trade partners. This study aims to analyze the economic diplomacy activities carried out by GPEI West Java in supporting exports and identifying the challenges and opportunities encountered. This research employs a qualitative method with a case study approach. Primary data were obtained through in-depth interviews with GPEI West Java representatives, while secondary data were collected from documents and reports related to export activities. The findings reveal that GPEI West Java actively engages in various activities, including export promotion through trade fairs, partnerships with international trade partners, business mentoring, and trade policy advocacy. However, several challenges persist, such as dependence on traditional trade partners, logistical and infrastructure constraints, the lack of supportive government policies, and limited technology adoption among business actors. In conclusion, GPEI West Java plays a significant role in economic diplomacy to strengthen exports and enhance the competitiveness of local products. However, further strategies are required, such as expanding market access to potential regions, increasing collaboration with the government on export policies, and leveraging digital technology to improve efficiency and competitiveness.